2020
DOI: 10.2147/cmar.s242193
|View full text |Cite
|
Sign up to set email alerts
|

<p>Metabolically Abnormal Obesity Increases the Risk of Advanced Prostate Cancer in Chinese Patients Undergoing Radical Prostatectomy</p>

Abstract: Background: To investigate the pathological risk of prostate cancer (PCa) according to the obesity and metabolic status of Chinese patients undergoing radical prostatectomy. Materials and Methods: We performed a retrospective cross-sectional study of 1016 patients with PCa who underwent radical prostatectomy and whose metabolic status and body mass index were examined. Multivariate logistic regression analysis was performed to examine the relationship between different metabolic obesity phenotypes and the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…A total of 14 articles regarding obesity and postoperative recurrence and prognosis were included (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). As shown in Figure 2, a significant heterogeneity among the studies was identified (I 2 =71.0%, P=0.000), so the REM was used.…”
Section: Comparison Of Postoperative Recurrence and Prognosis In Obese And Non-obese Pca Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 14 articles regarding obesity and postoperative recurrence and prognosis were included (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). As shown in Figure 2, a significant heterogeneity among the studies was identified (I 2 =71.0%, P=0.000), so the REM was used.…”
Section: Comparison Of Postoperative Recurrence and Prognosis In Obese And Non-obese Pca Patientsmentioning
confidence: 99%
“…A total of five articles were included to report the PSM condition of patients (12)(13)(14)17,21). Firstly, obvious heterogeneity was identified among the studies (I 2 =50.9%, P<0.001) (Figure 6A), so the REM was used for meta-analysis.…”
Section: Psm Conditions In Obese and Non-obese Pca Patients After Surgerymentioning
confidence: 99%
“…These results were similar to our overall results and did not change after adjusting for waist circumference (Table S2). Other prior studies used the MetS definition, excluding waist circumference (to separate other metabolic parameters from obesity) and observed stronger associations with the metabolically unhealthy phenotypes 11,19,20,23,39 . This suggests that other components of metabolic dysfunction, such as hyperglycaemia, hypertension and dyslipidaemia, may be driving the higher risk of ORC in the MUNW phenotype.…”
Section: Discussionmentioning
confidence: 92%
“…13 Considerable insights have been acquired in the association between MHO and the risks of chronic kidney disease 14 and prostate cancer. 15 However, studies on the association between MHO and LUTS/ BPH risk are few. Whether the risk of LUTS/BPH varies among different MetS-BMI phenotypes remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, controversy has surrounded the hypothesis that whether the unique MHO/MHOW phenotype is a harmless condition for adverse health outcomes 13 . Considerable insights have been acquired in the association between MHO and the risks of chronic kidney disease 14 and prostate cancer 15 . However, studies on the association between MHO and LUTS/BPH risk are few.…”
Section: Introductionmentioning
confidence: 99%